CaMKII-δ9 Induces Cardiomyocyte Death to Promote Cardiomyopathy and Heart Failure - Zhang, Mao; Zhang, Junxia; Zhang, Wenjia; Hu, Qingmei; Jin, Li; Xie, Peng; Zheng, Wen; Shang, Haibao; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Heart failure is a syndrome in which the heart cannot pump enough blood to meet the body's needs, resulting from impaired ventricular filling or ejection of blood. Heart failure is still a global public health problem and remains a substantial unmet medical need. Therefore, it is crucial to identify new therapeutic targets for heart failure. Ca2+/calmodulin-dependent kinase II (CaMKII) is a serine/threonine protein kinase that modulates various cardiac diseases. CaMKII-δ9 is the most abundant CaMKII-δ splice variant in the human heart and acts as a central mediator of DNA damage and cell death in cardiomyocytes. Here, we proved that CaMKII-δ9 mediated cardiomyocyte death promotes cardiomyopathy and heart failure. However, CaMKII-δ9 did not directly regulate cardiac hypertrophy. Furthermore, we also showed that CaMKII-δ9 induced cell death in adult cardiomyocytes through impairing the UBE2T/DNA repair signaling. Finally, we demonstrated no gender difference in the expression of CaMKII-δ9 in the hearts, together with its related cardiac pathology. These findings deepen our understanding of the role of CaMKII-δ9 in cardiac pathology and provide new insights into the mechanisms and therapy of heart failure.